2009
DOI: 10.1242/dev.027466
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Insulin receptor/Foxo signaling and dMyc activity during muscle growth regulates body size inDrosophila

Abstract: Drosophila larval skeletal muscles are single, multinucleated cells of different sizes that undergo tremendous growth within a few days. The mechanisms underlying this growth in concert with overall body growth are unknown. We find that the size of individual muscles correlates with the number of nuclei per muscle cell and with increasing nuclear ploidy during development. Inhibition of Insulin receptor (InR; Insulin-like receptor) signaling in muscles autonomously reduces muscle size and systemically affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
189
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 85 publications
14
189
0
2
Order By: Relevance
“…Ultimately, adult body size for D. melanogaster is determined by the size of the larva when it ceases feeding and enters metamorphosis, and largely by larval muscle size. Demontis and Perrimon (2009) showed that muscle size variation linked to modified insulin/TOR signaling affected adult size. Moreover, they showed that increased size occurred through increasing both nuclei number and DNA content of each individual nucleus (ploidy) through increased endoreplication, in addition to behavioral responses that modulate feeding and nutritional uptake (Conlon and Raff 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, adult body size for D. melanogaster is determined by the size of the larva when it ceases feeding and enters metamorphosis, and largely by larval muscle size. Demontis and Perrimon (2009) showed that muscle size variation linked to modified insulin/TOR signaling affected adult size. Moreover, they showed that increased size occurred through increasing both nuclei number and DNA content of each individual nucleus (ploidy) through increased endoreplication, in addition to behavioral responses that modulate feeding and nutritional uptake (Conlon and Raff 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the pathways regulating cellular growth play important roles in the control of endoreplication (Demontis and Perrimon, 2009;Pierce et al, 2008;Steiger et al, 2008). But what might be the advantages of cell growth mediated via polyploidy?…”
Section: Consequences Of Defective Endoreplication During Developmentmentioning
confidence: 99%
“…1A). Since the size of Drosophila larval muscles correlates with their number of nuclei (Demontis and Perrimon, 2009), we counted the number of nuclei in the DA3 muscle. Fewer nuclei were present in T2 and T3 (six on average) than in A1-A7 (eight on average) (Fig.…”
Section: Segment-specific Properties Of the Da3 Musclementioning
confidence: 99%